Scalable high performance radio frequency electronics based on large domain bilayer MoS2 - Qingguo Gao (Nature Portfolio, 2018)
Large area two-dimensional materials show promise for applications in DC and RF flexible electronics. Here, the authors report RF transistors based on chemical vapor deposited bilayer MoS2 with 23 GHz extrinsic maximum oscillation frequency, and gigahertz mixers on flexible polyimide substrates.